Experimental Analysis of the Effect of Wear Factors on Guide Vane of Hydraulic Turbine - Xiaoyi Zhao; Yuanjie Peng; Junxiang Yang; Minghui Ren; Xiaobing Liu (Machines, 2022)
In this paper, in order to study the wear of the guide vane of the hydraulic turbine, a test bench was built according to the actual internal flow of the hydraulic turbine of the power station. The value of the wear of the surface of the guide vane after polishing was reduced by 18.1 μm compared with that before polishing of P = 30.9 MW and by 12.5 μm at P = 42.8 MW. In order to reduce the influence of sediment wear on the guide vane, a 0.3 mm thick tungsten carbide coating was sprayed on its surface, and the wear of the guide vane after spraying tungsten carbide was obtained. The wear of the guide vane was reduced by about a factor of three to four times compared with that before spraying. In addition, according to the pH value of 6.73 of the river where the power station is located, the change of dissolved oxygen in the water body will affect the wear of the metal material on the surface of the guide vane, and the dissolved oxygen varies with the change of the water body temperature, so we simulated the temperature of the water body in the flood and the dry period of the power station, and got the wear amount of the polished guide vane in the flood period under the two working conditions of 28.1 μm and 47.3 μm, respectively. The wear amounts of the guide vane in the dry period were 25.2 μm and 43.9 μm, respectively. In addition, the service life of the guide vane before and after polishing and after tungsten carbide spraying was estimated based on the wear data obtained from the test, which provides a basis for power plant maintenance.